Neurofilament light chain: a biomarker for genetic frontotemporal dementia. Issue 8 (1st July 2016) - Meeter, Lieke H.; Dopper, Elise G.; Jiskoot, Lize C.; Sanchez‐Valle, Raquel; Graff, Caroline; Benussi, Luisa; Ghidoni, Roberta; Pijnenburg, Yolande A.; Borroni, Barbara; Galimberti, Daniela; Laforce, Robert Jr; Masellis, Mario; et al.
Abstract: Objective: To evaluate cerebrospinal fluid (CSF) and serum neurofilament light chain (NfL) levels in genetic frontotemporal dementia (FTD) as a potential biomarker in the presymptomatic stage and during the conversion into the symptomatic stage. Additionally, to correlate NfL levels to clinical and neuroimaging parameters. Methods: In this multicenter case–control study, we investigated CSF NfL in 174 subjects (48 controls, 40 presymptomatic carriers and 86 patients with microtubule‐associated protein tau ( MAPT ), progranulin ( GRN ), and chromosome 9 open reading frame 72 ( C9orf72 ) mutations), and serum NfL in 118 subjects (39 controls, 44 presymptomatic carriers, 35 patients). In 55 subjects both CSF and serum was determined. In two subjects CSF was available before and after symptom onset (converters). Additionally, NfL levels were correlated with clinical parameters, survival, and regional brain atrophy. Results: CSF NfL levels in patients (median 6762 pg/mL, interquartile range 3186–9309 pg/mL) were strongly elevated compared with presymptomatic carriers (804 pg/mL, 627–1173 pg/mL, P < 0.001), resulting in a good diagnostic performance to discriminate both groups. Serum NfL correlated highly with CSF NfL ( r s = 0.87, P < 0.001) and was similarly elevated in patients. Longitudinal samples in the converters showed a three‐ to fourfold increase in CSF NfL after disease onset. Additionally, NfL levels in patients correlated with disease severity, brain atrophy, annualized brain atrophy rate and survival. Interpretation: NfL in both serum and CSF has the potential to serve as a biomarker for clinical disease onset and has a prognostic value in genetic FTD.